PUBLIC SERVICE TRANSFORMATION AND AGRIBUSINESS MARKETING: INNOVATION ANALYSIS OF MAGESTY PUBLIC SERVICE PORTAL AND PLAZA TANI IN MAGELANG CITY - Sri Mulyani; Retno Dewi Pramodia Ahsani; Catur Wulandari (Universitas Riau Kepulauan, 2023)
This research aims to analyze the transformation of public services and agribusiness marketing through the innovation of the Magesty Public Services Portal and Plaza Tani in Magelang City. This research used a mixed method with qualitative and quantitative approaches—data collection techniques through interviews and surveys. The research subjects were application users, business actors, and Regional Apparatus Organizations in Magelang City who use the Magesty Public Services Portal and Plaza Tani services. The results showed that the transformation of public services and agribusiness marketing through the Magesty Public Services Portal and Plaza Tani innovation positively impacted the community and business actors in Magelang City. The recommendations are the need to improve service quality and more effective promotion to increase community and business participation in using these services.